1981
DOI: 10.1113/jphysiol.1981.sp013557
|View full text |Cite
|
Sign up to set email alerts
|

Calcium inward current and related charge movements in the membrane of snail neurones.

Abstract: SUMMARY1. Isolated and intracellularly perfused neurones from the snail Helix pomatia have been investigated under voltage-clamp conditions. Calcium inward current and asymmetric displacement current were examined.2. Two components of the asymmetric displacement current have been distinguished. One of them was irreversibly blocked by intracellular fluoride together with the calcium inward current. Another component (about 20 %) was not affected. The relation of the fluoride-sensitive asymmetric displacement cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
57
0
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 19 publications
20
57
0
1
Order By: Relevance
“…Activation of Ca2+ currents in other preparations such as snail neurones (Kostyuk et al 1981;Byerly & Hagiwara, 1982;Brown et al 1983;Byerly et al 1984a), pituitary cells (Hagiwara & Ohmori, 1982), rat sympathetic neurones (Belluzzi & Sacchi, 1989) and hippocampal neurones (Kay & Wong, 1987), has been shown to follow M2 kinetics. In contrast, chromaffin cell Ca2+ currents have been fitted with a two-exponential form (Fenwick et al 1982), cat sensory neurones Ca2+ currents were best fitted with a three-exponential form (Taylor, 1988 a) and a m5 form was required to fit Ca2+ currents in squid giant synapse (Llinas, Steinberg & Walton, 1981).…”
Section: Activation Of the Ca2+ Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of Ca2+ currents in other preparations such as snail neurones (Kostyuk et al 1981;Byerly & Hagiwara, 1982;Brown et al 1983;Byerly et al 1984a), pituitary cells (Hagiwara & Ohmori, 1982), rat sympathetic neurones (Belluzzi & Sacchi, 1989) and hippocampal neurones (Kay & Wong, 1987), has been shown to follow M2 kinetics. In contrast, chromaffin cell Ca2+ currents have been fitted with a two-exponential form (Fenwick et al 1982), cat sensory neurones Ca2+ currents were best fitted with a three-exponential form (Taylor, 1988 a) and a m5 form was required to fit Ca2+ currents in squid giant synapse (Llinas, Steinberg & Walton, 1981).…”
Section: Activation Of the Ca2+ Currentmentioning
confidence: 99%
“…Currents evoked from depolarized potentials should activate with roughly ml kinetics (Kostyuk et al 1981;Byerly et al 1984 a). This is so because a large fraction of Ca2+ channels is in a state that only needs to make one transition to reach the open state.…”
Section: Activation Of the Ca2+ Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…They do not contribute to the monotonically decaying Ca 2+ channel gating currents in neurons (Kostyuk et al, 1981), arthropod skeletal muscle (Gilly and Scheuer, 1984), and mammalian cardiac muscle (Bean and Rios, 1989), even though all these systems are activated by elevations of cytosolic Ca 2+. However, the latter systems are differently triggered indirectly by extracellular Ca 2 entry (Beuckelman and Wier, 1988;Fabiato, 1985;LopezLopez et al, 1995;Cannell et al, 1995;Sun et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ca channels are 'washed out' during intracellular perfusion (Kostyuk, Krishtal & Pidoplichko, 1981;Byerly & Hagiwara, 1982) and 'run down' irreversibly after formation of an isolated membrane patch (Fenwick, Marty & Neher, 1982;Cavalie, Ochi, Pelzer & Trautwein, 1983).…”
Section: Introductionmentioning
confidence: 99%